Instrumentation Systems for Subsidence Monitoring of Longwall Panels - John E. O’Rourke; Kevin M. O’Connor; Pamela H. Rey (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
INTRODUCTION The resurgence of coal mining activity in the United States, brought on by the spiraling costs of fossil fw1 energy in the Seventies, has come at a time of intense public concern for the quality of the environment. Notwithstanding pressure on our economy to develop alternate sources of fue1 energy to the import of oil, the legislatures of several states have reacted to public concern over the environment by passing strict regulations aimed at con- trolling the subsidence effect s of underground mining. Agencies of the federal government charged with assistance to the mining industry, including the Department of Energy and the Bureau of Mines, have sponsored a number of instrumentation and field measurement projects aimed at the development of subsidence prediction models that can aid the mine operator's task of subsidence control. There are good empirical models developed in Europe for subsidence prediction, but they were made possible by a large body of mining-induced subsidence data collected there over a long period of time. No com- parable subsidence data base exists in the United States, and consequently empirical modeling of subsidence is not a realistic approach for our near term needs. Moreover, the geologic and topographic diversity of the several coal regions in the United States is expected to necessitate the development of several empirical models, each one expected to be relevant to its own region. Because of the time and costs that are likely to be involved in an empirical modeling approach, it is considered more expedient and cost effective to develop a general, mechanistic model for subsidence prediction purposes. In order to develop such a model, it is necessary to investigate and quantify the mechanics of the subsidence process from the mine level up to the ground surface. The series of projects discussed in this paper are designed to achieve this objective and include the following work: (1) the identification of geotechnical instrumentation that will pro- vide mine level overburden and surface subsidence data. (2) a field demonstration of selected instruments, and (3) documentation of case histories for complete subsidence mechanics, using the demonstrated and preferred instruments. An identification of feasible instrumentation and monitoring techniques was completed by Woodward-Clyde Consultants (WCC) in 1977 (O'Rourke and others). This paper discusses a demonstration of those instruments at a mine in Utah, and at two subsequent projects, currently underway at longwall mines in Colorado and West Virginia. 'he latter two projects when complete will provide documented case histories of subsidence mechanics. The process of optimizing subsidence instrumentation and monitoring techniques to the conditions encountered during installation and monitoring for these underground mines is shown to be an evolving one, and one which has had some notable successes to date. INITIAL DEMONSTRATION The initial design and demonstration of selected monitoring systems was carried out at the SUFCO No. 1 mine, near Salina, Utah. The instrumented panel was approximately 152 m wide. 640 m long. and was 290 m to 320 m deep. The mined height of coal. seam averaged 2.4 m. The mining method was room and pillar using continuous mining machines. This method allowed some monitoring of the supported condition during development, and eventually allowed monitoring of a caved system when both chain pillars and room pillars were extracted on retreat. The two instrument systems shown on Table 1 were selected from the earlier feasibility report for demonstration at SUFCO No. 1. Collectively, the two systems, one for a fully-supported mining method and the other for a fully-caved method, incorporate most of the instrumentation to be found within all five systems listed in the earlier feasibility report. The instrumentation includes surface, subsurface and mine monitoring installations. All of the SUFCO instruments selected to meet the specifications of the general instrument types listed on Table 1 were manually operated. That is, data from the installed system could only be obtained while a person was there to physically observe or operate the system readout. Automatic data recording equipment was available for some installations, but the objectives were to keep the systems as simple as possible for the demonstration project. A complete description of the surface, sub- surface and mine level instruments, and the demonstration project results are given in WCC (1982), and selected features are discussed in this paper.